Acidic and thermal pre-treatments for anaerobic digestion inoculum to improve hydrogen and volatile fatty acid production using xylose as the substrate. (January 2020) - Mockaitis, Gustavo; Bruant, Guillaume; Guiot, Serge R.; Peixoto, Guilherme; Foresti, Eugenio; Zaiat, Marcelo
Abstract: Xylose is a by-product of lignocellulosic biomass processing for production of second-generation biofuels and could be suitable for bioproduct manufacturing. This paper describes an innovative approach that enables the system to achieve high yielding for hydrogen production. The study compared 4 physicochemical pre-treatments performed in an anaerobic mixed culture (acidic, thermal, acidic-thermal and thermal acidic) to achieve an inoculum with a high-efficiency xylose to hydrogen conversion under mesophilic conditions (30 °C). The acidic pre-treatment was the most efficient to select microorganisms able to produce hydrogen and volatile acid from xylose. Kinetics has shown that acidic pre-treatment had a hydrogen/xylose molar yielding factor of 1.57 (molar base) and a hydrogen maximum production rate of 253 mL H2 h −1 . Mass balance considered all possible metabolic pathways using xylose as a substrate. Anaerobic degradation of ethanol was the most active pathway for hydrogen production in all experiments, except for the control. Each pre-treatment performed for the original inoculum resulted in different microbiological profiles, but the genus Clostridium was the most abundant in all assays. Acidic pre-treatment stimulated the growth of organisms from the genera Peptostreptococcaceae, Truepera and Kurthia, which could be related to the better results in hydrogen production found in this condition. Graphical abstract: Image 1 Highlights: H2 production was related to Peptostreptococcaceae, Truepera and Kurthia Acidic pretreatment led to a higher, faster and more stable H2 production Thermal-acidic pretreatment was ineffective to stimulate H2 production All inoculum pretreatments inhibited CH4 production